How are market preferences shaped? The case of sovereign debt of stressed euro-area countries - Mamatzakis, Emmanuel; Tsionas, Mike G. (Journal of Banking & Finance, 2015)
This paper reveals the underlying market preferences for sovereign debt of distressed euro area countries. We employ a generalised flexible market loss, as it nests both the linear and the non-linear form, as a function of the ‘basis’, the difference between sovereign bond spread and the Credit Default Swap. Our evidence shows that market preferences lean towards pessimism for some countries, in particular Greece. Those preferences do not remain stable over time as they shift further towards pessimism post the Greek bail out in spring 2010. As part of sensitivity analysis we apply a multivariate loss function to account for contagion effects in forming market preferences among different sovereign bonds. We also examine the impact of specific financial and fiscal governance factors on market preferences. Our results suggest that the market closely monitor fiscal fundamentals so as to shape preferences.